2012
DOI: 10.1080/14763141.2011.637119
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wind on jumping distance in ski jumping – fairness assessed

Abstract: The special wind compensation system recently adopted by Fédération Internationale de Ski (FIS; International Ski Federation) to consider the effects of changing wind conditions has caused some controversy. Here, the effect of wind on jumping distance in ski jumping was studied by means of computer simulation and compared with the wind compensation factors used by FIS during the World Cup season 2009/2010. The results showed clearly that the effect of increasing head/tail wind on jumping distance is not linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…Summary effects were observed to be moderate, accounting for up to 4% of variance in the observed wind and round scores associations for all competitions. These results are in line with past findings that indicated that awarded wind compensation points are typically too low [7,8]. The observed effects were stronger for second round than for first round results, indicating stronger undercompensation for athletes that obtain higher classifications, although this difference did not reach nominal statistical significance.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Summary effects were observed to be moderate, accounting for up to 4% of variance in the observed wind and round scores associations for all competitions. These results are in line with past findings that indicated that awarded wind compensation points are typically too low [7,8]. The observed effects were stronger for second round than for first round results, indicating stronger undercompensation for athletes that obtain higher classifications, although this difference did not reach nominal statistical significance.…”
Section: Discussionsupporting
confidence: 91%
“…First, we did not investigate potential non-linearity of wind point effects on round scores. It has been shown, that effects of wind on jump length are not linear [7], which may have led to an underestimation of summary effects in the present study. However, we showed a robust meaningful negative association of wind points with round scores which may be interpreted as a lower threshold of the underestimation of wind compensation points.…”
Section: Limitationscontrasting
confidence: 56%
See 3 more Smart Citations